Jurnal Dialektika Kontemporer Beranda Tentang Kami Beranda Pengguna Cari Terkini Arsip Tesis Abstrak Beranda > volume 1 nomor 1 Tahun 2013 > Kawengian KOMUNIKASI PERKAWINAN ANTAR ETNIK (Studi Kasus Perkawinan Antar Etnik Mana - Deetje Anna Kawengian (Jurnal Ilmu Sosiologi Dialektika Kontemporer, 2013)
The purpose of this study is to identify the functional relationships of inter-ethnic families of Manado-Java couples; to determine the pattern of inter-ethnic communication in Manado-Java marriage; investigate factors that affect the survival Manado-Java inter-ethnic families. The results showed that: the functions of relationships were played by each member of the family with respect to situations and conditions in the household; Bahasa Indonesia is a language used as a means of communication in inter-ethnic marriages of Manado-Jawa tribes because it is easily understood by the whole family and easy to learn and tendency of people around informants using Bahasa Indonesia as the first language. Moreover, the factors that affect the survival of inter-ethnic family, namely: the income, established social strata, education of children, implementation of religious teachings and social environment.Keywords: Communication, Inter, Ethnic Marriage